GENDER AND LANGUAGE USE IN THE ENGLISH AND UZBEK MEDIA - Saidova Nilufar Anvar qizi (Journal of new century innovations, 2022)
Abstract: Studies suggest that the use of powerful speech makes the speaker appear more authoritative and credible. The article discusses the problem of gender linguistics in the aspect of its emergence and formation, primarily in the English- language linguistic literature; reviewed scientific literature, its analysis and brief description; analyzes the specifics of gender noisy speech on the material of the Uzbek language; the subject of the study was the Uzbek speech of the husband and wife, mother and son, mother and daughter in the form of brief dialogues, as well as material from artistic war literature; the dominant specificity of female speech is determined by shyness, belief in husband, diminutive affection, respect, deference, etc.; male Uzbek speech is characterized by some categoricality, brevity, combined with respect and attention ability to talk to the interlocutor. The results of our investigation indicate that there are few significant differences between the language used by women and that used by men in this particular situation.